Industrial training report: Telekom Malaysia / Nur Aqilah Abdull Hamid - Abdull Hamid, Nur Aqilah (Universiti Teknologi MARA, Perlis, 2023)
This report provides a summary of my experience interning at Telekom Malaysia, Ipoh Wisma in the Sales Management Department. The report includes information on the company's background, my reflections on the training I received, a SWOT analysis, discussion and recommendations, and a conclusion. My internship lasted for 6 months, from August 28, 2022 to February 10, 2023. This report was written by me, Nur Aqilah binti Abdull Hamid, a student of Bachelor in Business Administration (Hons) Finance from UiTM Arau, Perlis. I would like to thank my supervisor Puan Imtiaz binti Abu Bakar, the manager of Unifi Consumer Sales, Sales Management Perak, and my advisor Dr. Susilawani Ayob, a senior lecturer from UiTM Arau, Perlis, for their help and support throughout my internship. In this report contains of my profile as sum up in updated resume form and it is also summarize my background in previous education, personal information and also my skills and past experience job. This report also include the company profile such as Board Of Director, Mission & Vision and also their products that they offered in market. As to explain the outcomes of this industrial training journey, SWOT Analysis and Ratio Analysis was created. Find out what works well and what doesn't for the company in this section, while explaining new interpretations of the analysis based on the findings. A discussion and recommendation has been set up and elaborate in this report and also a conclusion that has been create. Finally, by evaluating positive and negative forces within and outside the company, the conclusion of the SWOT Analysis component helps the reader understand why the analysis should matter after reading the paper.